Efficacy of an organophosphorus hydrolase enzyme (OpdA) in human serum and minipig models of organophosphorus insecticide poisoning. (3rd May 2020) - Eddleston, Michael; Clutton, R. Eddie; Taylor, Matthew; Thompson, Adrian; Worek, Franz; John, Harald; Thiermann, Horst; Scott, Colin
Abstract: Objectives: Current therapeutic options for organophosphorus (OP) insecticide self-poisoning including atropine and oximes are inadequate and case fatality may exceed 20%. An OP hydrolase enzyme, OpdA, has been used for environmental cleansing of OP insecticides and prevented death in rat and non-human primate models of OP insecticide poisoning if given very quickly after exposure. We here tested OpdA's ability to break down OP insecticides in human serum and in clinically relevant minipig models of OP insecticide poisoning. Methods: Human serum was spiked with seven diverse WHO Class II OP insecticides (chlorpyrifos, quinalphos, diazinon, dimethoate, fenthion, phenthoate, and profenofos) and the effect of OpdA on degradation measured. The pharmacodynamic and clinical effects of OpdA treatment were studied in Gottingen minipigs orally poisoned with agricultural formulations of dimethoate EC40 or methyl parathion EC60; pharmacodynamic effects were also assessed in profenofos EC50-poisoned pigs. Results: OpdA effectively hydrolysed OP insecticides in human serum, with rates varying from 856 (SD 44) down to 0.107 (SD 0.01) moles of substrate hydrolysed/mole of enzyme/sec (kcat ) for quinalphos and phenthoate, respectively, although at rates 2–3 log orders less than found in vitro in buffered solution. It showed clinical benefit in minipig models, reducing the dose of noradrenaline required to sustain an adequate mean arterial pressure after dimethoate (mean 0.149 [SD 0.10] μg/kg/h vs. 1.07 [SD 0.77] μg/kg/h, p < .0001) and methyl parathion (mean 0.077 [SD 0.08] μg/kg/h vs. 0.707 [SD 0.49] μg/kg/h, p < .0001) poisoning. OpdA reduced blood OP insecticide concentration and acetylcholinesterase inhibition after poisoning by dimethoate, methyl parathion, and profenofos insecticides. Conclusions: In vitro incubation of OpdA in human serum showed hydrolysis of diverse OP insecticides, although at lower rates than found in buffer solutions. This activity results in clinical and pharmacodynamic efficacy in vivo against several OP insecticides. These results support the testing of OpdA in further animal models before considering human trials to determine whether it may become an urgently required novel therapeutic agent for OP insecticide self-poisoning.